EFFECT OF TEMPERATURE AND CONCENTRATION OF NaOH SOLUTIONS AS INHIBITORS ON IRON CORROSION RATE IN WATER MEDIA - Muthia Elma; Nurhalisah Nurhalisah; Afrisa Noor Hidayanti (Konversi, 2020)
Corrosion is a chemical phenomenon that often occurs in iron materials that are exposed or immersed in a medium either liquid or air. As a result of this corrosion is fragility and damage to the object so that the object cannot function properly. The purpose of this research is to prevent or slow down the occurrence of corrosion by adding chemicals called corrosion inhibitors which work by forming a protective layer on the surface of objects in the form of metal or iron.In this study, inhibitors were used in the form of NaOH solution with variations in the concentration of 0.1; 0.5; 1; 1.25; 1,5; 5 and 10 N are dissolved in water media and the iron immersion process is carried out at temperatures of 40, 45, and 50 °C. Soaked iron bars are measured for surface area and volume as well as weighing before and after the immersion process so that the corrosion rate is obtained with various variables used. Based on the research results obtained corrosion rate increases with increasing temperature and the addition of NaOH concentration inhibitors. Optimal temperature and concentration to inhibit the rate of iron corrosion is at an immersion temperature of 45 ° C and a concentration of 0.1 N NaOH with a corrosion rate of 0.084875 mpy.